Tribological Characteristics Of Electrical Discharge Coated Layers Using Quarry Dust Suspension - Liew, Pay Jun; Yap, Ching Yee; Othman, Intan Sharhida; Abdollah, Mohd Fadzli; Yan, Jiwang (Elsevier B.V., 2021)
In this research, a coating layer was formed on the tungsten carbide cobalt (WC-Co) substrate surface by using electrical discharge coating (EDC) with waste quarry dust powder suspension. The tribological test was carried out by using a micro pin-on-disc tribometer at a constant normal load (10N) and sliding speed (5 mm/s). The surface roughness, Vickers micro-hardness, coefficient of friction (CoF), wear weight loss, wear scar depth and wear track morphology of the coating layer were investigated and compared with the original surface of the WC-Co substrate in this study. The results indicated that under coating conditions of 5 A of peak current (Ip) and 300 μs of pulse on time (Ton), the Vickers micro-hardness increased by 28%, and the surface roughness, CoF, wear weight loss, and wear scar depth of coating layer reduced by 29%, 61%, 79%, 63%, respectively compared with the original WC-Co substrate. These results demonstrated that the coating layers produced by EDC with quarry dust waste powder suspension had good wear resistance, which could be beneficial to the cutting tool, mold and die industries.